P-8502—a new mu selective opioid receptor ligand - Ge Bang-lun; Zhang Hong-ping; Xu Yong-ping; Zhang Wei-jun (Acta Pharmacologica Sinica, 2016)
The analgesic potencies of 3-[beta-(p-amino)-phenethyl)-9 beta-methoxy-9 alpha-(m-methoxyphenyl)-3- azabicyclo [3,3,1] nonane (P-8502) and 3-[beta-(p-monoester fumarylamido)-phenethyl]-9 beta-methoxy-9 alpha-(m-methoxyphenyl)-3-azabicyclo [3,3,1] nonane (P-8511) were examined. The analgesic ED50 of P-8502 and P-8511 were 55 and 200 micrograms/kg (mice, ip, hot plate), and 30 and 95 micrograms/kg (rat, sc, tail flick), respectively. The duration of the analgesic action of P-8511 (about 4 h) was longer than that of P-8502 (about 1.5 h, rat, sc, tail flick). Binding assay showed that P-8502 had a high ratio of delta/mu, kappa/mu: IC50 (DPDPE)/IC50 (DAGO) = 399; IC50(DAD-LE)/IC50 (DAGO) = 1498; IC50 (kappa)/IC50 (DAGO) = 159. In conclusion, P-8502 appears to be a new mu selective opioid receptor ligand, whereas P-8511 has no such selectivity.